2000
DOI: 10.1021/jo000040l
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Stable Vesicles fromN- or 3-Alkylindoles:  Possible Evidence for Tryptophan as a Membrane Anchor in Proteins

Abstract: Twelve indole derivatives have been prepared and studied. Five were 1-substituted: 1, methyl; 2, n-hexyl; 3, n-octyl; 4, n-octadecyl; and 5, cholestanyloxycarbonylmethyl. Four were 3-substituted: 6, methyl; 7, n-hexyl; 8, n-octyl; and 9, n-octadecyl. Three were disubstituted as follows: 10, 1-n-decyl-3- n-decyl; 11, 1-methyl-3-n-decyl; and 12, 1,3-bis(n-octadecyl)indole. Sonication of aqueous suspensions afforded stable aggregates from 3-5 and 8-12. Laser light scattering, dye entrapment, and electron microsco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 57 publications
2
24
0
Order By: Relevance
“…A key factor is probably the steric encumbrance of the side chain, since Trp is believed to be a very good anchor point in the membrane. 20,21 In an attempt to improve the potency of DS1(1-15)-NH 2 we added a Lys residue to the N-terminus. Recent findings indicated that acylation of dermaseptin S4 fragments with long chain fatty acids, with or without an amino function in their structures, is well tolerated in terms of antimicrobial activity and is instrumental in modulating the potency and spectrum of activity in different assay conditions.…”
Section: Resultsmentioning
confidence: 99%
“…A key factor is probably the steric encumbrance of the side chain, since Trp is believed to be a very good anchor point in the membrane. 20,21 In an attempt to improve the potency of DS1(1-15)-NH 2 we added a Lys residue to the N-terminus. Recent findings indicated that acylation of dermaseptin S4 fragments with long chain fatty acids, with or without an amino function in their structures, is well tolerated in terms of antimicrobial activity and is instrumental in modulating the potency and spectrum of activity in different assay conditions.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, substitution of tryptophan may severely affect the insertion capacity of TM peptides. In many TM domains, including the active domain of the TAP inhibitor ICP47, tryptophan residues are located at the interfacial region, where they serve as a membrane anchor (40,(44)(45)(46)(47).…”
Section: The Journal Of Immunologymentioning
confidence: 99%
“…An examination of the KcsA voltage gated potassium channel from Streptomyces lividans suggests that the indole residues of all the tryptophans in the structure occur at the insulator-midpolar boundary [45]. Tryptophan is the rarest of the 20 common amino acids and appears to play an important role as a stabilizing element [46][47][48] (Fig. 6).…”
Section: Design Criteria For Hydraphilesmentioning
confidence: 99%